Attitude toward Nature in School and University Students from Megalopolis - Mukhortova E.A (Moscow State University of Psychology and Education, 2021)
The problem of attitude to nature and especially to plants, despite a large number of works, remains still actual. This paper describes the study of gender and age aspects of the attitude towards nature among modern teenagers and youth living in a megapolis. An assumption was made that college students as compared with schoolchildren, as well as girls compared with boys, may have a more positive attitude to nature, and their connection with nature is stronger. The study used «Naturaphil» (S.D. Deryabo, V.A. Yаsvin) method and the questionnaire «People and plants» (S.K. Nartova-Bochaver, E.A. Mukhortova). 144 respondents were surveyed, 102 females and 42 males, including 72 collegestudents (Mage=20.56) and 72 eighth grade school students (Mage=14.0). The age- and gender-related characteristics are described of the attitude to nature, the structure of the attitude to nature and plants in teenagers and students is presented. The leading component in the structure of relations to nature in the entire sample is the perceptual-affective component; the less in intensity were the scales actional, practical, and cognitive. The results obtained indicate that in youth, the strength of connection with nature may appear higher than in adolescence. Certain gender differences were also established: the indicators of the questionnaire «People and plants» are significantly higher in the female group. Girls were characterized by a more positive attitude to the plant world: they obtained a higher overall score, as well as on the scales of Aesthetics, Connection with nature and Ecology.